Experiences of using very low energy diets for weight loss by people with overweight or obesity: a review of qualitative research. (24th August 2018) - Harper, C.; Maher, J.; Grunseit, A.; Seimon, R. V.; Sainsbury, A.
Summary: Although very low energy diets (VLEDs) are the most successful non‐surgical, non‐pharmacological treatment for obesity, they are underutilized, and little is known about experiences of people using VLEDs for weight loss. This systematic review synthesizes qualitative studies investigating participants' experiences of undertaking a VLED composed of total meal replacement products to lose weight. Of the 4, 911 articles screened, three studies met criteria for inclusion. Thematic synthesis was used to analyse the study findings. Health and appearance were the main motivators to use a VLED for weight loss. Adherence was facilitated by group support meetings, rapid weight loss and ease of use of the diet. Being part of a clinical trial gave a sense of accountability and further reason to adhere to a VLED, and the VLED itself was well accepted by users. Barriers to adherence, such as temptations and social occasions, were overcome by avoidance and distraction strategies. In conclusion, this qualitative synthesis of users' experiences of VLEDs shows that VLEDs are well accepted and positively viewed by users. More in‐depth research could facilitate understanding of how this weight loss strategy influences the weight maintenance period, in order to facilitate better long‐term results.